History of scoria‐cone eruptions on the eastern shoulder of the Kenya–Tanzania Rift revealed in the 250‐ka sediment record of Lake Chala near Mount Kilimanjaro. (21st August 2019) - Martin‐Jones, Catherine; Lane, Christine; Van Daele, Maarten; Meeren, Thijs Van Der; Wolff, Christian; Moorhouse, Heather; Tomlinson, Emma; Verschuren, Dirk
ABSTRACT: Reconstructions of the timing and frequency of past eruptions are important to assess the propensity for future volcanic activity, yet in volcanic areas such as the East African Rift only piecemeal eruption histories exist. Understanding the volcanic history of scoria‐cone fields, where eruptions are often infrequent and deposits strongly weathered, is particularly challenging. Here we reconstruct a history of volcanism from scoria cones situated along the eastern shoulders of the Kenya–Tanzania Rift, using a sequence of tephra (volcanic ash) layers preserved in the ~250‐ka sediment record of Lake Chala near Mount Kilimanjaro. Seven visible and two non‐visible (crypto‐) tephra layers in the Lake Chala sequence are attributed to activity from the Mt Kilimanjaro (northern Tanzania) and the Chyulu Hills (southern Kenya) volcanic fields, on the basis of their glass chemistry, textural characteristics and known eruption chronology. The Lake Chala record of eruptions from scoria cones in the Chyulu Hills volcanic field confirms geological and historical evidence of its recent activity, and provides first‐order age estimates for seven previously unknown eruptions. Long and well‐resolved sedimentary records such as that of Lake Chala have significant potential for resolving regional eruption chronologies spanning hundreds of thousands of years.